Jaminan Kehilangan Pekerjaan (JKP) dalam Perspektif Belanja Negara - Zellius Ragiliawan; Beni Teguh Gunawan (Jurnal Ketenagakerjaan, 2021)
The labour paradigm changes along with the presence of the industrial revolution 4.0. The impact on employment is a change in several indicators, includingflexibility in working hours, wages, and work relations. Law No. 11 of 2020 concerning Job Creation is considered to be one of the government’s breakthrough to face industry 4.0. One of the points stipulated in the regulation is the existence of job loss insurance (JKP) as a safety net along with the high flexibility. Government Regulation No. 37 of 2021 concerning the Implementation of Job Loss Security regulates that one of the components of worker contributions comes from the central government. This study aims to estimate the increase in government’sexpenditure in line with this scheme. The results of the analysis using BPS data show that the average JKP contribution out of the central government has the potential to increase by 28.39 percent per year. This number is predicted to continue to increase along with the narrowing of the boundaries between formal and informal workers.